Screening of local Brassica varieties for salt tolerance at germination and seedling establishment stage - Sehrish; Rauf, Mamoona; Khan, Asad Ali; Gul, Humaira; Yaseen, Tabassum; Butt, ZahidAli; Latif, Muhammad; Khushnood Ur Rehman (Journal of Pure and Applied Agriculture, 2023)
An abiotic factor that causes reduction in the productivity of the crops in different parts of the world is salinity which creates changes in different physiological and metabolic processes depending on the duration and severity of the stress condition in which the plant is present. The purpose of the study was to investigate the effect of salt stress on germination and seedling growth of different varieties of Brassica (NUYTM, Hyola (2), Abasin-95, NIFA Raya, NIFA Gold, Datura-e-NIFA, NUYTC-13, AARI Canola, NUYTC-16, and NUYTM-17). In this experiment, 10 sterilized seeds of six different varieties of brassica were arranged in petri dishes with 5ml of different concentrations of NaCl (0, 50mM, and 150mM) and each concentration has three replicates. After 7 days the experiment was terminated and different parameters such as (root length, shoot length and vice versa). The current result showed that length of root and shoot, fresh and dry weight of root and shoot, relative water content, vigor index decreased while root shoot ratio, shoot weight ratio, and root weight ratio was increased in NIFA Raya variety. It was concluded that NIFA Raya and NUYTM-17 showed more salt-tolerant than the other cultivars. © 2021 Department of Agricultural Sciences, AIOU